The Development of Plant Encyclopedia Based on Datebase in Adiwiyata Senior High School - Asyifa, Bella Firdha; Rudyatmi, Ely; Abdullah, Muhammad (FMIPA UNNES, 2019)
SMA Negeri 1 Cawas does not have a digital inventory of plants. Digital inventory can be stored for  long time and updated. The study aims to develop an encyclopedia of-based plants database in adiwiyata schools. Research design with Research and Development (RnD). The steps include analysis of potential and problems; data collection; product design; design validation by media experts (lecturers and media experts BPMPK) and material experts (expert classification lecturers); revision 1; small-scale trials (for biology teachers, Wakakur and responses by class XI MIA students 2); revision 2; large-scale trials (all students of class XI MIA); revision 3; and the final product. Based on the results of the study there were 46 plant species. Encyclopedia design (Ensiya) includes templates, systems coding, and finalization program. Ensiya is used to facilitate the management of plant inventories. Revision 1, carried out on the program name, label, motivation, and location of the outbox. Revision 2 of the program name; label box size; motivation box and outbox. The results of a large-scale trial, Ensiya obtained a very feasible assessment by students and received positive responses. Revision 3, program name font; picture box; motivation, and the location of the outbox. Conclusion of this study, that  the plant encyclopedia (Ensiya) in the database-based adiwiyata school was successfully developed using Microsoft Visual Basic Express. Ensiya digital documents, 165 MB file size, accessed offline, transferred between computers with data transfer, and can be changed by studying Microsoft Visual Basic Express programming, is very valid and very feasible.